Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Dengan Media Pembelajaran Petualangan Ular Tangga Materi Sumber Energi di Kelas II Sekolah Dasar - Hasanah, Lailatul; Anggraini, Dilla Puspa; Dwi Maharani, Putri Aprilia; Setiyawan, Hery (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The TGT model is one of the learning approaches that involves group work and healthy competition between students. Snakes and ladders media is used as a fun and familiar learning aid for students, so that it can increase their interest and motivation to learn. This study aims to determine the effect of the Team Games Tournament (TGT) type cooperative learning model with snakes and ladders adventure learning media on the learning outcomes of grade 2 Elementary School students on energy source material. This study uses a quantitative approach with a quasi-experimental research design and uses a pretest-posttest control group design. The techniques used in this study are using the normality test, homogeneity test and t-test. The research sample consisted of two classes, namely the experimental class (using the TGT model and snakes and ladders media) and the control class (using conventional learning). The instrument used was an essay test of 10 questions for the pretest and posttest. The results of data analysis using the t-test showed a significant difference between student learning outcomes in the experimental class and the control class. Thus, it can be concluded that the application of the TGT model with snakes and ladders media has a positive effect on improving student learning outcomes.